Diabetes distress and depression among patients with type 2 diabetes: A cross-sectional study - Saad, Ahmad; Younes, Zeina; Abuali, Alaa; Farooqi, Muhammad; Hassoun, Ahmed (Journal of Diabetes and Endocrine Practice, 2021)
Purpose: The purpose of this study is to identify the rates of diabetes distress and depression in patients with Type 2 diabetes and to explore the relationship between glycemic control, depression, and diabetes distress. Patients and Methods: One hundred and fifteen adults with Type 2 diabetes were recruited for this cross-sectional study from the Dubai Diabetes Center in Dubai, United Arab Emirates. The Arabic version of the Diabetes Distress Scale was used to assess diabetes distress, and the Arabic version of the Beck Depression Inventory-II scale was used to assess depression symptoms. Results: Our study population consisted of 63 males (54.8%) and 52 females (45.2%). We found that, out of this study population, 54.3% had uncontrolled diabetes with glycosylated hemoglobin (HbA1c) >7% (53 mmol/mol), 54.8% exhibited diabetes distress, and 29.6% showed depression. Using a combined oral and insulin treatment was found to be significant independent predictors of poor glycemic control as defined by an HbA1c >7% (53 mmol/mol). Conclusion: This study has identified psychosocial issues as a significant health problem among adult patients with type 2 diabetes and offers data confirming the relevance of diabetes distress and depression among them. This finding can help clinicians have a better understanding of the extent to which psychosocial issues influence diabetes management so as to develop effective and appropriate treatment approaches.
Keywords: Depression; diabetes; diabetes distress; United Arab Emirates